Performance of Indian Batsmen in the 2023 World Cup Squad - A Survival Analysis Approach - Munusamy Ramakrishnan; Natarajan Viswanathan; Ramanujam Ravanan (Statistica)
The game of cricket is enjoyed by millions of fans across the Globe. India is perusing the game like  anything. Though, at present, many local tournaments like IPL were conducted in India, the ability of the batsmen and their patterns of scoring runswere reflected by the amount of runs they score in the international ODI’s played between Countries. The runs scored by batsmen with information on whether they are “batting-first” or “chasing” throws more light on the patterns of runs-scoring. Also, the order in which the batsmen bat is also taken into consideration in this study. Further, the performance of batsmen varies across different teams of the game. More uncertainty exists in the run-scoring pattern. All these make it difficult for predicting the runs scored by a batsman. Survival analysis comes handy in predicting the probabilities of such events. The study, in this perspective, considers nine batsmen selected from the one-day Indian world cup squad 2023. The information of these batsmen, particularly the runs scored by them against different countries were used to find the probabilities of their run-scoring pattern. The study uses Kaplan-Meier’s product limit estimator, Cox Proportional Hazard model and Accelerated Failure Time Parametric model for analysing the patterns. Log-rank test is used for comparing survival distributions. Also, the study compares the relative performance of selected batsmen. Data, updated as on 4th September 2023, were used for each of the batsman under consideration. The analysis has been carried out using R program.